Event-based privacy-consensus control for multiagent systems: An enhanced framework for fault-tolerance and protection against eavesdropping - Hu, Xiaoyan; Ye, Dan (Applied mathematics and computation, 2025)
This paper investigates the consensus problem of privacy protection for multi-agent systems (MASs) under conditions of compound faults. We develop a fault-tolerant observer that utilizes intermediate variables to estimate both the system state and compound faults, specifically addressing sensor and actuator faults in the physical layer of the system. To safeguard the privacy of communication data at the network layer, a dual protection encoding and decoding strategy is proposed. Furthermore, an intermittent event-triggered mechanism (ETM) is introduced to mitigate the computational and communication burdens imposed by the encoding algorithms. Discrete-time combination measurement values are employed to enhance the generalizability of the ETM. Within the framework of encryption and decryption, fault-tolerant consensus control algorithm is designed to counter two types of eavesdroppers, thereby achieving privacy consensus for MASs while addressing challenges associated with physical layer faults. In the end, a simulation of an island microgrid (MG) with five distributed generators (DGs) is developed to confirm the efficacy of the suggested approach. •Adopting a dual key encoding scheme to enhance the resistance to eavesdropping attacks.•The problem of composite physical layer faults has been solved based on an intermediate state observer.•The introduction of intermittent event triggering mechanism reduces the computational burden caused by encoding technology.•An enhanced robust privacy protection algorithm has been established for linear continuous time multi-agent systems.